Uma viagem ao coração da América do Sul : Karl Von Den Steinen (1884-1885) - Ramos, Sérgio Henrique Pereira de Souza (2020)
This dissertation aims analyze the representations of Mato Grosso, included in the first work of the German scientist, Karl von den Steinen (1855-1929), entitled Central Brazil. Expedition in 1884 for the exploration of the Xingu River, published in Germany in 1886 and translated in Brazil in 1942 by Catarina Baratz Cannabrava. The work is organized beyond the translator's note and preface, in nine chapters. In view of this, it was intended to analyze his first trip to South America in the years 1884-1885, seeking to understand him as a scientist, explorer who traveled to different regions of the South American continent, with more scientific than commercial purposes. The research presented intends to clarify, issues that involve the traveler, seeking to understand how a European observed and represented his experiences during his trajectory towards the heart of South America. The theoretical-methodological support will be given by the New Cultural History, understanding the representations as part of a narrative discourse built from the imagination and subjectivity of this European traveler.